Investigation of Power Flow Tracing Strategy Using an Index in a Transmission System with Solar PV for Congestion Management - Alias M.R.N.M.; Verayiah R.; Yin L.J. (Institute of Electrical and Electronics Engineers Inc., 2023)
Electric power transmission; MATLAB; Silicon compounds; Solar power generation; System stability; IEEE 14 bus system; LQP _LT; Photovoltaic sizing; Photovoltaics; Solar photovoltaics; Three-point loss; Transmission systems; Voltage stability index; Voltage-stability index; Weakest bus; Electric load flow